Sedges : Cyperus to Scleria - Mohlenbrock, Robert H. (Book collections on Project MUSE., 2001)
This second edition of Sedges: Cyperus to Scleria brings up to date the identification of species of sedges in Illinois (except Carex) since publication of the first edition in 1976. During the intervening years, several additions to the sedge flora of Illinois have been made, and many new distributional records have been added. Also, a large number of nomenclatural changes have taken place, resulting in several alterations of scientific names. New illustrations have been provided for all of the additions. In his introductory.